Lacunary harmonic summability in neutrosophic normed spaces - Aral, Nazlim Deniz; Kandemir, Hacer Sengul; Et, Mikail (Univ Nis, Fac Sci Math, 2024)
In this study, we introduce the concept of strongly lacunary (H, 1) convergence in the neutrosophic normed spaces. We investigate a few fundamental properties of this new concept.
Keywords: Cauchy sequence; lacunary convergence; neutrosophic normed space